NETWORKING ENTERPRISE MANAGEMENT STRUCTURE - L. I. Podderеgina (Наука и техника)
The paper presents new basic criteria and recommendations on formation of networking enterprise management structure at national enterprises that make it possible to improve economic efficiency of their intra-industrial relations.